Physical activity measurement tools among college students in intervention studies: A systematic review - Sanying Peng; Ahmad Zamri Khairani; Abubakar Rabiu Uba; Fang Yuan (PLoS ONE, 2025)
Background Assessing the impact of interventions on college students’ physical activity (PA) requires the use of reliable and valid measurement tools. However, the tools employed in existing studies and their respective reliability and validity are not well-documented. This review aims to systematically evaluate the PA measurement tools utilized in interventions targeting college students and to assess the quality of their measurement properties. Methods A comprehensive search was conducted across five databases (MEDLINE, Cochrane, Embase, Web of Science, PsycInfo) to identify studies on PA interventions among college students, using specific inclusion criteria. The screening of literature and data extraction were independently performed by two authors, focusing on the types of PA measurements used and their measurement properties. Results A total of 52 studies, involving 63 different PA measurement tools, were included. Of these, 28 studies used self-report tools, 14 employed objective tools (with one study using two different objective tools), and 10 combined both methods. The International Physical Activity Questionnaire (IPAQ) emerged as the most frequently used self-report tool, while pedometers and accelerometers were the primary objective tools. Despite frequent references to reliability and validity, few studies provided specific evidence regarding measurement properties such as internal consistency and criterion validity, particularly those tailored to the studied population. Conclusion The majority of PA measurement tools for college students rely on self-reported data, with limited verification of their reliability and validity. For a more accurate assessment of PA intervention effects, it is recommended to adapt the widely recognized IPAQ to specific contexts and incorporate objective tools like accelerometers, which offer practical and precise measurement within college settings.